GENDER DIFFERENCES IN CONVERSATIONAL STYLE IN “APA KABAR INDONESIA TALK SHOW NEWS PROGRAM ON TVONE” - Yulia Warda (Fakultas Agama Islam Universitas Al Washliyah, 2020)
The objectives of this research are (1) to find out the features of conversational style are used by male and female presenters in “Apa Kabar Indonesia” and (2) to find out the different ways of communication between male and female presenters that realized in “Apa Kabar Indonesia”. (3) to describe the reason why do male and female presenters used style differently in the talk show news. This research uses qualitative research method especially the applied theory. The source of the data is the video tape of “Apa Kabar Indonesia” which is gathered by down load in internet . The data are analysed based on Miles and Huberman who have provided three models of analyzing the data in this study, namely; data reduction, data display and also conclusion drawing. The validity of the data was taken by applying theory triangulation and data triangulation, while in this study has more than one theory to answer the problems of this study and data triangulation is gained from two points, namely; time and person. Time is concluded the existence of “Apa Kabar Indonesia” and person is concluded the existence of participants. Based on the analysis, it is found that: (1) male presenters are dominantly uttered amount of talk with the total 80 utterances, while female presenters uttered it with the total 55 utterances, interruption feature are used by male presenters with the total 18 utterances and female presenters uttered it with the total 5 utterances. Male presenters expressed conversation support with the total 10 utterances and female presenters expressed it with the total 9 utterances. The phenomena of conversation support in “Apa Kabar Indonesia” male presenters didn’t uttered tentativeness, whereas female presenters uttered it with the total 1 utterance, the last one is compliment male presenters uttered it with the total 1 utterance and female presenters expressed it with the total 3 utterances. (2) In “Apa Kabar Indonesia” male presenters are able to communicate by female-like strategies vice versa female presenters are able to communicate by male-like strategies. (3) Male and female speakers used style differently because they have different characteristics in growing up in social life.